Placental polyp: a rare cause of iron deficiency anemia - Campos, Fernando Peixoto Ferraz de; Simões, Ricardo Santos; Felipe-Silva, Aloísio; Gonzales, Milena Degaspari; Ilário, Eder Nisi (Autopsy and Case Reports, 2011)
Placental polyps are defined as pedunculated or polypoid fragments of placentaor ovular membranes retained for an indefinite period of time into the uterus afterabortion or child birth. An important cause of retention is placental accretism, anabnormal adherence of the placenta into the uterine wall. Chronic cases are rarelyreported in the literature. In these cases, the placental retention in the immediatepostpartum is not followed by heavy bleeding what makes the diagnosischallenging. We report a rare case of iron-deficiency anemia in a multiparous29-year-old female patient two years after the last delivery. She sought medicalcare with clinical symptoms of anemia and recent menses alterations. Therewas no history of abortion. On gynecological examination, there was a twofoldenlarged uterus, and the pelvic ultrasound revealed an image compatible with anendometrial polyp. She underwent open hysterectomy because of uncontrollablebleeding followed by hypotension after curettage. The histolopathologicexamination revealed a partially hyalinized and necrotic placental polyp.